Determinants of Exchange Rates And Inflation to Stock Prices in Companies Listed LQ45 Indices on Indonesia Stock Exchange - M. Agustiswan Saputra; Vikka Putri (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
This study aims to determine the effect of Exchange Rate and Inflation on Stock Price. The population in this study is Go-Public companies from the LQ45 Index listed on the Indonesia Stock Exchange during the period 2017-2019. The sample selection technique in this study is purposive sampling. Thirty-six companies have been acquired that meet the criteria of the research sample. The results showed that Exchange Rate and Inflation partially or simultaneously did not have a significant effect on the dependent variable, namely the Stock Price of LQ45 Index Companies Listed on the Indonesia Stock Exchange for the 2017-2019 period.